Swelling of mucoadhesive electrospun chitosan/polyethylene oxide nanofibers facilitates adhesion to the sublingual mucosa. (15th August 2020) - Stie, Mai Bay; Gätke, Johan Ring; Wan, Feng; Chronakis, Ioannis S.; Jacobsen, Jette; Nielsen, Hanne Mørck
Graphical abstract: Highlights: Stability of chitosan/PEO nanofibers in water depends on the DDA of chitosan. Chitosan interacts strongly with mucin from bovine submaxillary glands. Chitosan with the highest DDA (96 %) interacts most strongly with mucin. Swelling of chitosan/PEO nanofibers induces adhesion to sublingual mucosa. Abstract: Mucoadhesive chitosan-based electrospun nanofibers are promising candidates for overcoming challenges associated with sublingual drug delivery, yet studies focusing on evaluating the mucoadhesive properties of nanofibers for sublingual administration are limited. The aim was to elucidate the mucoadhesive properties of chitosan/polyethylene oxide (PEO) nanofibers focusing on how the degree of deacetylation (DDA, 53–96 %) of chitosan influenced their morphological and mucoadhesive properties. The mechanism of mucoadhesion was explained by the intermolecular interactions of chitosan with mucin from bovine submaxillary glands using quartz-crystal microbalance with dissipation monitoring and by adhesion of the nanofibers to ex vivo porcine sublingual mucosa. An increase in chitosan DDA improved the morphological stability of the nanofibers in water, but did not contribute to altered mucoadhesive properties. This study demonstrates excellent mucoadhesive properties of chitosan/PEO nanofibers and shows that the strong mucoadhesiveness of the nanofibers is attributed to their swelling ability.